Modelling and simulation to prevent in snowboarding - Senner, V.; Lehner, S.; Michel, F. I.; Brügger, O. (Modelling and simulation in sport and exercise, 2020)
This chapter deals with the tools and equipment used in sport and that are therefore subject to design and optimization. There is a broad spectrum of such tools, ranging from bobsleighs more expensive than luxury cars to shoes tested in special laboratories for optimal adaption to special moving conditions. Moreover, particular tools like prostheses can help not only to improve movement but also to enable movement at all. Different types of models are combined by Senner, Lehner, Michel and Brügger in order to answer a specific research question in the area of prevention of overloads in snow sports: "Which type of design or which functional elements of snowboard wrist protectors can reduce stress in the wrist and forearm bones in a typical backward fall situation, in particular for the target group children and adolescents?". Again, biomechanical models are the focus of this chapter. In particular, various computer-aided engineering tools are introduced and discussed.